2018
DOI: 10.14423/smj.0000000000000823
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Term Combination LT4 and LT3 Therapy for Improving Hypothyroidism and Overall Quality of Life

Abstract: Guidelines from the American Thyroid Association and the American Association of Clinical Endocrinologists suggest monitoring thyroid-stimulating hormone and serum-free thyroxine to make clinical decisions for starting and monitoring therapy with their mainstay treatment of levothyroxine monotherapy. Although this monotherapy provides adequate control of symptoms for the majority of the population, a strong subset of the population continues to complain of hypothyroidism despite normal thyroid-stimulating horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 42 publications
0
30
0
1
Order By: Relevance
“…In our analysis of patient forum posts, DTE use was commonly associated with improvements in overall well-being, a finding supported in the trial subgroup analyses, where those patients who preferred DTE had significant improvements in the general health questionnaire-12 and thyroid symptom questionnaire [27]. Improvements in quality of life were also previously in an observational study of 100 patients prescribed T3-containing thyroid hormone replacement (LT4 + LT3 or DTE) after receiving LT4 monotherapy, indicating reports of improved quality of life in 93% and 89% of the DTE and LT4/LT3 populations, respectively, as assessed by the Medical Outcomes Study Short Form-20 (SF-20) questionnaire [28]. In this study, more than 70% of the participants receiving DTE reported being as "healthy as anybody they knew", 87% said "feeling calm and peaceful", and 88% reported "being a happy person".…”
Section: Discussionmentioning
confidence: 71%
“…In our analysis of patient forum posts, DTE use was commonly associated with improvements in overall well-being, a finding supported in the trial subgroup analyses, where those patients who preferred DTE had significant improvements in the general health questionnaire-12 and thyroid symptom questionnaire [27]. Improvements in quality of life were also previously in an observational study of 100 patients prescribed T3-containing thyroid hormone replacement (LT4 + LT3 or DTE) after receiving LT4 monotherapy, indicating reports of improved quality of life in 93% and 89% of the DTE and LT4/LT3 populations, respectively, as assessed by the Medical Outcomes Study Short Form-20 (SF-20) questionnaire [28]. In this study, more than 70% of the participants receiving DTE reported being as "healthy as anybody they knew", 87% said "feeling calm and peaceful", and 88% reported "being a happy person".…”
Section: Discussionmentioning
confidence: 71%
“…This is despite the fact that ATA guidelines for the treatment of hypothyroidism conclude that there is insufficient evidence to support prescribing T3-containing therapies (2, 4), but in keeping with more recent recommendations from British and Italian Societies (2022). It is difficult to identify original published data that might account for the current willingness to prescribe combination therapy, and published data about preference or improvement of symptoms with such therapy is entirely from uncontrolled (23), sparsely documented (25) or small studies (24). It has become increasing common to involve patients in their own care and to incorporate joint physician-patient decision-making in the management of many conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At the present, other than the one additional clinical study already mentioned (19), there have not been additional randomized clinical trials of combination therapy that might potentially alter physician prescribing. However, some studies about patient preference have been added to the literature (2325). Previous studies from our group have shown that patient and physician characteristics affect the tendency to prescribe combination therapy (26, 27).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacodynamics was one of the main aspects in promoting a shift to the synthetic hormone LT4 from earlier T3-containing alternatives such as DTE, although comparative clinical assessment was widely lacking at that time 5,6. Although the safety profile of LT4 is well-known, few studies have addressed the long-term safety of LT3 administration 167,168. Over 17 years of observation, Leese did not identify increased clinical risks of atrial fibrillation, cardiovascular disease, or fractures for LT3, compared to LT4 167.…”
Section: Adverse Drug Effectsmentioning
confidence: 99%